Photoreceptor calcium sensor proteins in detergent-resistant membrane rafts are regulated via binding to caveolin-1. (July 2018) - Vladimirov, Vasiliy I.; Zernii, Evgeni Yu; Baksheeva, Viktoriia E.; Wimberg, Hanna; Kazakov, Alexey S.; Tikhomirova, Natalya K.; Nemashkalova, Ekaterina L.; Mitkevich, Vladimir A.; Zamyatnin, Andrey A.; Lipkin, Valery M.; Philippov, Pavel P.; Permyakov, Sergei E.; et al.
Graphical abstract: Highlights: NCS proteins contain conservative caveolin-1 binding site in their C-terminal domain. Recoverin, NCS1, GCAP1, and GCAP2 co-localize with caveolin-1 in ROS membrane rafts. NCS proteins bind to scaffolding domain of caveolin-1 at low calcium. Caveolin-1 enhances activity of Ca 2+ -free GCAP2 towards ROS guanylate cyclase-1. Caveolin-1 increases Ca 2+ affinity of recoverin by affecting its Ca2+-myristoyl switch. Abstract: Rod cell membranes contain cholesterol-rich detergent-resistant membrane (DRM) rafts, which accumulate visual cascade proteins as well as proteins involved in regulation of phototransduction such as rhodopsin kinase and guanylate cyclases. Caveolin-1 is the major integral component of DRMs, possessing scaffolding and regulatory activities towards various signaling proteins. In this study, photoreceptor Ca 2+ -binding proteins recoverin, NCS1, GCAP1, and GCAP2, belonging to neuronal calcium sensor (NCS) family, were recognized as novel caveolin-1 interacting partners. All four NCS proteins co-fractionate with caveolin-1 in DRMs, isolated from illuminated bovine rod outer segments. According to pull-down assay, surface plasmon resonance spectroscopy and isothermal titration calorimetry data, they are capable of high-affinity binding to either N-terminal fragment of caveolin-1 (1–101), or its short scaffolding domain (81–101) via a novel structural site. In recoverin this site is localized in C-terminal domain in proximity to the third EF-hand motif and composed of aromatic amino acids conserved among NCS proteins. Remarkably, the binding of NCS proteins to caveolin-1 occurs only in the absence of calcium, which is in agreement with higher accessibility of the caveolin-1 binding site in their Ca 2+ -free forms. Consistently, the presence of caveolin-1 produces no effect on regulatory activity of Ca 2+ -saturated recoverin or NCS1 towards rhodopsin kinase, but upregulates GCAP2, which potentiates guanylate cyclase activity being in Ca 2+ -free conformation. In addition, the interaction with caveolin-1 decreases cooperativity and augments affinity of Ca2 + binding to recoverin apparently by facilitating exposure of its myristoyl group. We suggest that at low calcium NCS proteins are compartmentalized in photoreceptor rafts via binding to caveolin-1, which may enhance their activity or ensure their faster responses on Ca 2+ -signals thereby maintaining efficient phototransduction recovery and light adaptation.